GAMBARAN KETERAMPILAN MENYIKAT GIGI PADA ANAK USIA 5 TAHUN (Politeknik Kesehatan Kemenkes Bandung, 2020)
Introduction: Dental health problems in children are still high due to lack of dental health maintenance behavior. Good and proper tooth brushing skills are important factors for the maintenance of dental health so as to prevent dental health problems in children. Purpose: This study aims to determine the tooth brushing skills in the 7 areas of the tooth surface in children aged 5 years before and after being educated to brush their teeth with individual education using a jaw model. Methods: This research method is a descriptive observation conducted in Bandung Regency.Research subjects were 9 children aged 5 years. Teeth brushing skills were observed before being given education to find out the early brushing skills in children and after being educated to find out changes in brushing skills in children. Result: The results indicate that the tooth brushing skills of respondents before being educated are still do not know the tooth brushing skills on the surface of the teeth facing the cheeks and the surface of the teeth facing the tongue and palate. After being given an education, their tooth brushing skills improved but there were still brushing skills that most respondents found difficult to get used to, namely brushing skills on the surface of the inner teeth facing the ceiling. Conclusion: There is an increase in the ability to brush teeth in 7 areas of children's tooth surface after being given education on brushing teeth.